Giant Pyonephrosis Due to Calculus of Ureter: A Case Report - Singgih, Nicholas Andrian; Lionardi, Stevan Kristian; Mintardi, Mintardi (Majalah Kedokteran Bandung, 2023)
Giant pyonephrosis (GP) is a rare and severe form of pyonephrosis characterized by a massive enlargement of the affected kidney due to the accumulation of infected fluid. This study presents case of a 51-year-old male patient with giant pyonephrosis who underwent nephrectomy as treatment. The clinical manifestations of giant pyonephrosis are nonspecific, necessitating the use of imaging and laboratory techniques to aid in diagnosis. Nephrectomy is the preferred treatment option for these patients. One week after nephrectomy, the laboratory results showed improvements. Making the right treatment decision is challenging in this particular case.